Artificial Intelligence and Islamic Religious Education: Integrating Qur’anic Ethical Principles to Foster Responsible Digital Literacy among Muslim Students - Ahmad Nabriz; Helene Knudstad; Rahmat Ullah; Ajoy Chandra; Abubaker Kashada (PT Barkah Ilmi Fiddunya, 2026)
The rapid development of artificial intelligence (AI) has significantly transformed the educational landscape, particularly in how students access, process, and disseminate information in digital environments. This study aims to examine the integration of Qur’anic ethical principles in fostering responsible digital literacy among Muslim students in the era of artificial intelligence. It focuses on key Qur’anic concepts such as tabayyun (verification of information), ethical communication, and responsibility in knowledge acquisition as moral foundations for digital literacy in contemporary education. By integrating these ethical principles with emerging technologies, the study seeks to propose a framework for promoting responsible digital behavior among students, this research employs a library research method using a qualitative approach through systematic analysis of scholarly literature related to artificial intelligence in education, digital literacy, information ethics, and Qur’anic perspectives on knowledge and communication. Data sources consist of peer-reviewed journal articles, books, and academic publications from the last five to ten years. The collected literature was analyzed using content analysis and conceptual synthesis to identify key themes linking AI-based learning environments with Qur’anic ethical teachings relevant to responsible digital engagement, the findings indicate that integrating Qur’anic ethical values provides a strong moral framework for developing responsible digital literacy in AI-supported learning environments. Principles such as tabayyun encourage critical verification of information, while Qur’anic guidance on responsible speech and knowledge fosters ethical digital communication and critical thinking. The novelty of this study lies in proposing a conceptual integration between AI-based digital literacy and Qur’anic ethical epistemology, bridging technological innovation with Islamic ethical values to cultivate morally responsible digital citizen.